Surface-Associated Host Proteins on Virulent Treponema pallidum - Alderete, John F. (1979)
A surface coat of host serum proteins was detected on virulent Treponema pallidum by sodium dodecyl sulfate-gel electrophoresis. The loosely associated serum proteins could be removed by repeated washings in a protein-free medium. Washed T. pallidum retained the ability to readsorb numerous host proteins from rabbit serum as well as iodinated rabbit or human albumin. In addition, various avidly associated host serum proteins including albumin, α(2)-macroglobulin, transferrin, ceruloplasmin, immunoglobulin G, immunoglobulin M, and C3 were identified on the outer envelope of washed treponemes by an immunoadsorbent technique with protein A-bearing staphylococcus. Hyaluronidase treatment did not remove the avidly associated host proteins from the surface of washed treponemes, whereas trypsin treatment resulted in decreased levels of agglutination. Electrophoretic patterns of trypsin-treated treponemes showed that treponemal proteins as well as adsorbed host proteins were released concurrently by protease digestion. Reacquisition studies involving α(2)-macroglobulin and transferrin suggested the presence of noncompetitive binding sites for serum proteins on the treponemal outer envelope. Finally, differences among the T. pallidum preparations from individual rabbits with respect to incorporation of [(35)S]methionine, extent of agglutination with antisera, and length of time required for removal of avidly associated host proteins by trypsin treatment indicated biological variability among the treponemal populations.